2014
DOI: 10.1523/jneurosci.3979-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Hypothalamic Paraventricular Nucleus and the Organum Vasculosum Lateral Terminalis in the Control of Sodium Appetite in Male Rats

Abstract: Angiotensin II (AngII) and aldosterone cooperate centrally to produce a robust sodium appetite. The intracellular signaling and circuitry that underlie this interaction remain unspecified. Male rats pretreated with both deoxycorticosterone (DOC; a synthetic precursor of aldosterone) and central AngII exhibited a marked sodium intake, as classically described. Disruption of inositol trisphosphate signaling, but not extracellular-regulated receptor kinase 1 and 2 signaling, prevented the cooperativity of DOC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…The hormone regimen used in the present study was previously demonstrated to increase sodium ingestion in the Veh/AngII and DOC/AngII groups and to significantly water intake in the Veh/AngII condition (Grafe et al, 2014). Here, the progressive ratio operant task was used to compare the effort rats are willing to exert for sodium ingestion after these hormone treatments.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…The hormone regimen used in the present study was previously demonstrated to increase sodium ingestion in the Veh/AngII and DOC/AngII groups and to significantly water intake in the Veh/AngII condition (Grafe et al, 2014). Here, the progressive ratio operant task was used to compare the effort rats are willing to exert for sodium ingestion after these hormone treatments.…”
Section: Resultsmentioning
confidence: 70%
“…In contrast, humoral AngII acts initially on AngII type 1 (AT1) receptors in circumventricular organs, such as the subfornical organ and the organ vasculosum of the lateral terminalis (Lind et al, 1985; McKinley et al, 1992b; Tanaka et al, 1986; Weiss and Hatton, 1990). Mineralocorticoids exert minor up-regulation of AT1 receptor levels and AT1 signaling (Grafe et al, 2014; Shelat et al, 1999a; Shelat et al, 1998; Shelat et al, 1999b). As a parallel mechanism, mineralocorticoids may exert a cooperative behavioral effect with AngII by acting elsewhere in a broader circuit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While lesion of just the SFO does not affect the DOCAsalt increase in blood pressure, fluid intake, or sodium appetite, genetic ablation of AT 1A R from the SFO attenuates DOCA-salt hypertension and polydipsia (52,103). Thus these and other data support a functional synergism between ANG II and aldosterone (42,148,149). These studies also highlight the importance of the SFO and its target nuclei to mediate central ANG II effects through AT 1 R.…”
Section: Stimulators Of the Brain Ras And Physiological Effects Of Sfmentioning
confidence: 62%